The Effectiveness of Using Interactive Simulation in Kindergarten Children’s Acquisition of Physics Concepts - Al-Mohtaidi, Reham; Mustafa Jwaifell; Yahya Al-Dhaimat; Almazaydeh, Laiali (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The study aimed to investigate the effectiveness of using interactive simulation in developing some physics concepts in a sample of kindergarten children. To achieve the study objective, a semi-experimental method was used. The study sample consisted of the (45) kindergarten children of ‘The Pink Bird’ Kindergarten in Petra. They were randomly divided into two groups: an experimental group of (22) children who were taught using interactive simulation, and a control group of (23) children who were taught by the traditional way. Contrary to the traditional method of education, the study results proved the effectiveness of interactive simulation in the acquisition of physics concepts among kindergarten children. It was also found that around 61% of the change in the dependent variable (physical concepts) is due to the use of interactive simulation in teaching. Eventually, the study included a set of recommendations in the light of its results.